Meaningful Values of Life of Women Suffering Perinatal Losses - Nevoenna, Olena; Kadyhrob, Kateryna (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2021)
The article considers the issues of modern perinatal psychology related to the problem of experiencing an existential crisis, namely, the features of the meaningful life orientations of women, who are at the reproductive age, with the experience of desired pregnancy. We have conducted a comparative analysis of the meaningful life orientations in women who have experienced perinatal losses and women who have children without perinatal losses in the anamnesis. We have recorded significant differences in the life values of "active life". Women who have suffered perinatal losses have a significantly higher rate of this value. We explain this by the fact that the activity of these women is mediated by their life goals of high personal importance, the most significant of which are childbearing and childbirth, while the activity of mothers without perinatal losses in the anamnesis corresponds with their hedonist meanings. Existential meanings of women with pregnancy or newborn losses are related to their perceptions of family happiness and need for it, while women whose pregnancies have ended successfully, the meanings are caused by the importance of love and freedom, the latter is the subject to conscious women's control. The importance of freedom, as an opportunity to realize their own goals, of women who suffered from perinatal losses due to the need to fulfill their life purpose and search for sense of life, in women mothers without loss in the anamnesis the value of life itself is in all its displays. In general, women who have suffered perinatal losses, despite strong ambivalence due to the feeling of failure in childbearing, tend to build their lives according to their meaningful life orientations, the priority of which are motherhood, activity in behavior and altruistic self-realization. In our opinion, it makes lives of women more organized and productive, allows them to restore the idea of themselves as people whose lives have formed.